2019
DOI: 10.4149/bll_2019_131
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient sleep duration is associated with worse self-rated health and more psychosomatic health complaints in adolescents

Abstract: OBJECTIVE: To investigate the association between sleep duration and self-rated health and psychosomatic health complaints in a representative sample of Slovak adolescents aged 13 and 15 years. BACKGROUND: According to empirically supported recommendations adolescents age 13 to 18 years old should sleep 8 to 10 hours per 24 hours on a regular basis to promote optimal health. METHODS: We used data from the Health Behaviour in School-aged Children (HBSC) study conducted in 2018 in Slovakia comprising 8,405 adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…Previous studies confirmed our findings that excessive use of EDs was associated with reduced and insufficient sleep duration [ 20 , 21 , 23 , 50 ] or even insomnia [ 24 ]. The association between insufficient sleep duration and emotional and behavioural problems has also been confirmed by several cross-sectional, experimental studies, as well as by systematic reviews [ 25 , 26 , 37 , 38 , 39 , 51 , 52 , 53 ]. Although most of the studies were cross-sectional and used subjective measures for sleep duration, the evidence from the experimental studies and systematic reviews suggests that the relationship between lack of sleep and emotional and behavioural problems in adolescents is likely to be casual and thus supports our findings that the effect of ED consumption on emotional status and behaviour of adolescents is not direct, but mediated through sleep duration.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Previous studies confirmed our findings that excessive use of EDs was associated with reduced and insufficient sleep duration [ 20 , 21 , 23 , 50 ] or even insomnia [ 24 ]. The association between insufficient sleep duration and emotional and behavioural problems has also been confirmed by several cross-sectional, experimental studies, as well as by systematic reviews [ 25 , 26 , 37 , 38 , 39 , 51 , 52 , 53 ]. Although most of the studies were cross-sectional and used subjective measures for sleep duration, the evidence from the experimental studies and systematic reviews suggests that the relationship between lack of sleep and emotional and behavioural problems in adolescents is likely to be casual and thus supports our findings that the effect of ED consumption on emotional status and behaviour of adolescents is not direct, but mediated through sleep duration.…”
Section: Discussionmentioning
confidence: 70%
“…High ED intake is also associated with unhealthy behavior, such as reduced and insufficient sleep and breakfast skipping in adolescents [ 7 , 17 , 21 , 22 , 23 , 24 ]. Evidence shows that 30 to 50% of adolescents sleep less than recommended 8 h [ 25 , 26 , 27 ], and the prevalence of sleep problems varies between 10 to 20% in adolescents [ 28 , 29 , 30 ]. According to the large studies conducted in Europe and other countries [ 31 , 32 , 33 , 34 , 35 ], a high proportion of adolescents were classified as breakfast-skippers, ranging from 40–50% (China, Austria, Slovenia) to 10–20% (Spain, Poland, Japan).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the duration or quality of sleep, caused either by a shift work or lifestyle changes, affect among others the immune system through activation of NF-κB (nuclear factor κB), which is responsible for the expression of pro-infl ammatory genes (5,24). Sleep disturbances relate to an increased rate of non-specifi c subjective symptoms (25), as well as an increased risk of development of various gastrointestinal disorders including IBD, where the exacerbation of the disease deteriorates sleep quality, which furthermore promotes infl ammation, resulting in a self-sustaining feedback-loop (4,26).…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous research found that more adolescents had problems with lack of sleep than with falling asleep. Furthermore, the amount of sleep decreased with age and the problems with falling asleep and EBPs were more common in girls than boys [8,36].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal sleep quantity and quality is essential for the mental health, adequate functioning and well-being of adolescents [4,5]. However, 30% to 50% of adolescents sleep less than recommended [6][7][8][9] and the prevalence of sleep difficulties, manifested as difficulties in falling or staying asleep, range from 10% to 20% in adolescents [10][11][12][13][14][15]. According to the recommendations of American Academy of Sleep Medicine (AASM), adolescents of 13 to 18 years old should sleep 8 to 10 h per 24 h on a regular basis to promote optimal health [16].…”
Section: Introductionmentioning
confidence: 99%